Vacuum heat treatments of titanium porous structures - Ghouse, S; Oosterbeek, RN; Mehmood, AT; Vecchiato, F; Dye, D; Jeffers, JRT (Elsevier, 2021)
Additive manufacturing (AM) of Ti-6Al-4V enables rapid fabrication of complex parts, including porous lattices which are of interest for aerospace, automotive, or biomedical applications, however currently the fatigue resistance of these materials is a critical limitation. Engineering the alloy microstructure provides a promising method for increasing fatigue strength, but conventional heat treatment procedures are known to produce atypical results for AM and porous samples, and must therefore be optimised for these materials. Using vacuum heat treatment, microstructures comparable to those observed for conventional wrought and heat treated alloys were achieved with porous AM Ti-6Al-4V. Fine lamellar microstructures were produced using sub-transus heat treatment at 920 °C, while coarse lamellar microstructures were produced using super-transus heat treatment at 1050 °C or 1200 °C. Increasing the heat treatment temperature increased the elastic modulus from 2552 ± 22 MPa to a maximum of 2968 ± 45 MPa, due to strut sintering increasing the effective strut thickness, and removal of prior β-grain orientation. Heat treatment eliminated the brittle α’ martensite phase in favour of an α + β mixture, where the phase boundaries and β-phase provide greater resistance to crack propagation. Super-transus heat treatments increased the α-lath size which typically reduces crack propagation resistance, however strut sintering reduced surface crack initiation sites, increasing the fatigue strength by 75% from 4.86 MPa for the as-built material to a maximum of 8.51 MPa after 1200 °C heat treatment. This work demonstrates that vacuum heat treatment is effective at tuning the micro- and macro-structure of porous AM Ti-6Al-4V, thereby improving the crucial fatigue resistance.